2008
DOI: 10.1523/jneurosci.4258-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Protects Cultured Cortical Neurons from Lipopolysaccharide-Induced Cell Death via Regulation of NR1 Expression

Abstract: Inflammation is involved in some neurodegenerative disorders. NMDA glutamate receptors play an important role in neuronal development. Here, we show that NR1 expression in the cerebral cortex and primary neurons of rats was upregulated after lipopolysaccharide (LPS) treatment. This increase in NR1 expression was considered to be strongly associated with hypoxia-inducible factor-1␣ (HIF-1␣) activation because the treatment of primary neurons with either echinomycin or small interfering RNA (siRNA) targeting HIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…The NMDA-NR 1 promoter sequence has at least one known HIF-1 transcription complex binding site 25 . This suggests that the HIF-1 transcription complex may bind to the NMDA-NR 1 promoter and increase transcription of NMDA-NR 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The NMDA-NR 1 promoter sequence has at least one known HIF-1 transcription complex binding site 25 . This suggests that the HIF-1 transcription complex may bind to the NMDA-NR 1 promoter and increase transcription of NMDA-NR 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Tbr-1 is a neuron-specific T-box factor (Hsueh et al, 2000) that may play a role in neurogenesis and induction of GluN1. GluN1 expression is subject to control by hypoxia-inducible factors that function under stress conditions, especially during hypoxia (Yeh et al, 2008). Based on GluN1 up-regulation after lipopolysaccharide injection into the prefrontal cortex and in cultured neurons, the predicted cis hypoxia response elements were localized within the Grin1 promoter.…”
Section: B Kainate Receptors Grik1 To Grik5mentioning
confidence: 99%
“…This supports the finding that the longer the neurons stayed in the culture media in the experimental hypoxic groups, the greater the extent of the neuronal cell injuries and death (Francis and Wei 2010;Du et al 2012;Prentice et al 2012). A possible explanation for this phenomenon is that prolonged hypoxia may cause a significant release and accumulation of endogenous glutamate which causes glutamate-induced toxicity and hence death of the cells (Nyakas et al 1996;Yeh et al 2008;Francis and Wei 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that oxidative stress can cause neurodegeneration associated with enhanced susceptibility to apoptosis due to the activation of pro-apoptotic genes (Gibson and Huang 2002;Du et al 2012). Hypoxia-induced oxidative stress can cause neurite retraction leading to neurodegeneration and neuronal loss similar to that found in Alzheimer's disease (Banasiak et al 2000;de la Monte et al 2000;Yeh et al 2008;Prentice et al 2011;López-Hernández et al 2012).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation